2021
DOI: 10.3390/biomedicines9080854
|View full text |Cite
|
Sign up to set email alerts
|

Post-Treatment with Amorfrutin B Evokes PPARγ-Mediated Neuroprotection against Hypoxia and Ischemia

Abstract: In this study, we demonstrate for the first time that amorfrutin B, a selective modulator of peroxisome proliferator-activated receptor gamma—PPARγ, can protect brain neurons from hypoxia- and ischemia-induced degeneration when applied at 6 h post-treatment in primary cultures. The neuroprotective effect of amorfrutin B suggests that it promotes mitochondrial integrity and is capable of inhibiting reactive oxygen species—ROS activity and ROS-mediated DNA damage. PPARγ antagonist and Pparg mRNA silencing abolis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 43 publications
2
18
0
Order By: Relevance
“…The effect was accompanied by substantial decreases in neurotoxicity and neurodegeneration measured by LDH release and Fluoro-Jade C staining of damaged cells, respectively. Previously, we used the same cellular models of perinatal asphyxia and stroke, i.e., 6-h hypoxia or ischemia followed by 18-h reoxygenation, which reflected the major features of brain pathologies in vivo (Wnuk, Przepiórska et al 2021), including oxidative stress due to enhanced ROS production, oxidative DNA damage, neurotoxicity, and neurodegeneration caused Since PaPE-1 has only been recently synthesized, no relevant reports are available to compare the results of our present studies. The beneficial effects of ER agonists, particularly estrogens, on brain tissue undergoing hypoxia and/ or ischemia have been extensively reported; however, only a few research reports have focused on membrane ERs, mainly GPER1 (previously GPR30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect was accompanied by substantial decreases in neurotoxicity and neurodegeneration measured by LDH release and Fluoro-Jade C staining of damaged cells, respectively. Previously, we used the same cellular models of perinatal asphyxia and stroke, i.e., 6-h hypoxia or ischemia followed by 18-h reoxygenation, which reflected the major features of brain pathologies in vivo (Wnuk, Przepiórska et al 2021), including oxidative stress due to enhanced ROS production, oxidative DNA damage, neurotoxicity, and neurodegeneration caused Since PaPE-1 has only been recently synthesized, no relevant reports are available to compare the results of our present studies. The beneficial effects of ER agonists, particularly estrogens, on brain tissue undergoing hypoxia and/ or ischemia have been extensively reported; however, only a few research reports have focused on membrane ERs, mainly GPER1 (previously GPR30).…”
Section: Discussionmentioning
confidence: 99%
“…The cells were placed in a prewarmed and humidified hypoxia modular incubator chamber (Billups-Rothenberg, Inc., CA, USA) with 95% N 2 /5% CO 2 for 6 h. The O 2 level was measured with an oxygen analyzer (Greisinger, Germany) and reached less than 0.5%. After 6 h of hypoxic/ ischemic conditions, i.e., at the reoxygenation period, the culture medium was replaced immediately with standard medium for 18 h (Wnuk, Przepiórska et al 2021).…”
Section: Experimental Models Of Hypoxia and Ischemiamentioning
confidence: 99%
“…The hypoxic conditions were evoked by placing the cultures in a prewarmed and humidified hypoxia modular incubator chamber (Billups-Rothenberg, Inc., CA, USA) with 95% N 2 /5% CO 2 for 6 h as previously described [ 24 ]. The O 2 level in the chamber was measured with an oxygen analyzer (Greisinger, Germany) and reached less than 0.5%.…”
Section: Methodsmentioning
confidence: 99%
“…Our recent study showed that amorfrutin B, administered even 6 h after injury, evokes a strong neuroprotective effect against hypoxia and ischemia by increasing the viability of neuronal cells and mitochondrial integrity as well as reducing oxidative stress and the accompanying DNA damage. The neuroprotective effect of amorfrutin B involves PPARγ activation and epigenetic modifications, which position this compound among the most promising anti-stroke therapeutics [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…34 Mouse primary neuronal cultures treated with amorfrutin B led to hypermethylation of the peroxisome proliferator-activated receptor gamma (PPARγ) gene, reduced PPARγ expression, and prevented neuronal death following oxygen-glucose deprivation (OGD). 35 These examples indicate that DNA methylation is involved in regulating genes involved in stroke pathophysiology (Figure 2). However, more studies are needed to understand the extent to which global DNA methylation changes impact gene expression after cerebral ischemia.…”
Section: Epigenetic Mechanisms In Strokementioning
confidence: 99%